2010
DOI: 10.1055/s-0030-1258245
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Testing of Polyamine Vectored Iron Chelators

Abstract: Iron chelators have been shown to control the growth of cancer cells in culture by sequestering exogenous iron in the media. Thus, the ligands prevent cellular access to the metal. However, because transferrin provides iron to tumor cells in animals, chelators have not been effective antitumor agents. Polyamine chelator conjugates in which the polyamine vectored ligands into cells were far more active than the free chelators themselves. However, the free ligands were not released from the vector once in the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Such a concept has been reported in previous studies on the synthesis and the biological properties of a chelating Deferiprone-type moiety linked to spermine. 41 In addition, other studies revealed that homospermidine−anthracene conjugates were more selectively recognized by the PTS than spermine derivatives. 38 Instead, we chose the hydroxyquinoline moiety, found in the iron chelator O-Trensox, which has a higher affinity for iron than Deferiprone.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Such a concept has been reported in previous studies on the synthesis and the biological properties of a chelating Deferiprone-type moiety linked to spermine. 41 In addition, other studies revealed that homospermidine−anthracene conjugates were more selectively recognized by the PTS than spermine derivatives. 38 Instead, we chose the hydroxyquinoline moiety, found in the iron chelator O-Trensox, which has a higher affinity for iron than Deferiprone.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The efficiency of the polyamine transport system (PTS) is also greatly increased in tumoral cells. This property is of potential interest for targeting antitumor agents [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Based on these observations, we have developed a new generation of iron chelators, the Quilamines, in which an 8-hydroxyquinoline chelating subunit is grafted onto polyamine vectors, in order to vectorize the iron chelator inside the cancerous cell with an overactive PTS [29].…”
Section: Polyamine a Vector For Anticancer Agentsmentioning
confidence: 99%